2008
DOI: 10.1021/ac8011818
|View full text |Cite
|
Sign up to set email alerts
|

Encoded and Multiplexed Surface Plasmon Resonance Sensor Platform

Abstract: We present a flexible new sensor system that combines the joint advantages of (i) discretely functionalized, code-bearing, microparticles and (ii) label-free detection using grating-coupled surface plasmon resonance. This system offers the possibility of simultaneously investigating the real-time binding kinetics of a variety of molecular interactions. One single multiplexed assay could employ a wide range of immobilization chemistries, surface preparation methods, and formats. Thus, the new system offers a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The most well-studied systems involve alkanethiols grown on Au surfaces [8,9,78,79,104,117,122], although sulphur also shows a strong affinity towards the other noble/ coinage metals, including Ag [9], Pt, Cu, Hg and Pd. Au is most often chosen due to its inertness and resilience to oxidation-so we shall start by discussing this system.…”
Section: Self Assembled Monolayersmentioning
confidence: 99%
“…The most well-studied systems involve alkanethiols grown on Au surfaces [8,9,78,79,104,117,122], although sulphur also shows a strong affinity towards the other noble/ coinage metals, including Ag [9], Pt, Cu, Hg and Pd. Au is most often chosen due to its inertness and resilience to oxidation-so we shall start by discussing this system.…”
Section: Self Assembled Monolayersmentioning
confidence: 99%
“…The purpose of adding casein after the enzyme adsorption is to prevent false signal caused by the binding of this blocking protein on Au nanopyramids not covered by the antibody. 27 In summary, we have demonstrated that templated nanopyramid arrays with sharp nanotips exhibit strong SPR due to the efficient localization of electromagnetic field. The templating technology is scalable and compatible with standard microfabrication, promising for developing sensitive chemical and biological sensors for real-time and label-free detection.…”
mentioning
confidence: 78%
“…Copyright 2008 Springer Science + Business Media); (M) Optical image of octagonal graticles with optical gratings etched into the surface and codes cut into the sides for multiplexing. (Reprinted with permission from Ref 52. Copyright 2008 American Chemical Society.…”
Section: Strategies For Particle Encodingmentioning
confidence: 99%